Thermal Structure Beneath the Tarim Craton and Its Tectonic Implications - Xu, Xi; Xiong, Shengqing; Tanaka, Akiko; Zheng, Qiang; Kuang, Xingtao; Zhu, Xiaoying; Zhou, Daoqing; Zheng, Qifang; Wan, Jianhua; Yu, Xuezhong; Wang, Baodi (Frontiers in Earth Science, 2021)
The lateral distribution of the magnetic layer beneath the Tarim Basin and its environs was estimated from spectral analysis using the newest high-resolution aeromagnetic dataset of mainland China, which is enlarged by EMAG2. As a thermal structure proxy, the Curie point depth (CPD) provides a comprehensive view of a crust-scale thermal regime, which accounts for the depth at which magnetite becomes paramagnetic, and the correspondence of the CPD with the tectonic regime indicates that the CPD is useful for delineating the regional crustal thermal structure. Furthermore, lateral variations in CPD provide useful insights into the lithospheric thermal state of the Tarim Basin and its environs and can be related to ancient and active tectonics, such as geothermal activity, seismicity, and mineral-petroleum generation. In the Tarim interior, the NW domain covering the Bachu Uplift and its surrounding areas corresponds to the minimum magnetic CPD signature geometry of this area, which is most likely linked to the Permian Tarim plume-lithosphere interaction. In contrast, the remaining domains are characterized by large CPD values (up to 50 km), which are floored by a Precambrian basement without the Permian magmatism destruction. Moreover, the estimated CPD values are consistent with surface heat flow measurements with an inverse correlation, which can assist in identifying the potential area for mineral deposits and hydrocarbon fields. Earthquakes are mostly concentrated in the gradient and transition zones of the Curie surface, suggesting that these abrupt variation domains in the crustal thermal structure act as a secondary mechanism for earthquake generation.